The Role of Guidance and Counseling (BK) Teachers in Cultivating Students' Growth Mindset in the Midst of Digital Academic Competition - Samsidar, Samsidar (Journal of Therapia, 2025)
Digital transformation in education has a significant impact on the dynamics of learning and students' academic expectations. Amidst increasingly tight academic competition and pressure to excel in the digital space, students need to strengthen an adaptive and resilient mentality. This article discusses the strategic role of Guidance and Counseling (BK) teachers in fostering a growth mindset, the belief that abilities can be developed through effort and learning in high school students. This study uses a qualitative approach with a case study method in three high schools in Indonesia. The results of the study indicate that structured counseling interventions, personal support from BK teachers, and the integration of self-development programs into the curriculum can significantly improve students' growth mindset. This article recommends strengthening the capacity of BK teachers in digital literacy and positive psychology as a systematic effort to face the challenges of increasingly complex digital academic competition.